Oral health-related quality of life in patients with periodontitis: a systematic review and meta-analysis - Slowik, Joanna; Panasiuk, Anna; Kaczor, Marcin; Wnuk, Marcin (Frontiers in Oral Health, 2025)
ObjectiveThis study aimed to comprehensively evaluate the impact of periodontitis on Oral Health-Related Quality of Life (OHRQoL) using the OHIP-14 questionnaire. A quantitative meta-analysis was conducted to estimate the average effect size, taking into account the characteristics of periodontitis and the features of control groups. Additionally, associations between OHRQoL and periodontitis were explored based on participant demographics and clinical factors.MethodsWe systematically searched the PubMed, Embase, and Scopus databases up to March 8, 2024. Studies included in the analysis assessed OHRQoL in patients with periodontitis (exposed group) compared to non-periodontitis individuals (non-exposed control group). A valid periodontitis diagnosis required Clinical Attachment Loss (CAL) and Pocket Probing Depth (PPD) assessments during full-mouth clinical examinations. The choice of meta-analysis model was based on an assessment of heterogeneity. The quality of the included studies was assessed using the tool developed by The National Heart, Lung, and Blood Institute (NHLBI).ResultsNine studies, encompassing 2,287 individuals, met the inclusion criteria. Periodontitis significantly affected the mean OHIP-14 total scores compared to controls [Weighted Mean Differences WMD random = 6.11 (95% CI: 4.23, 7.99), p < 0.0001], with substantial heterogeneity. Subgroup analysis did not reveal significant regional variations. Restricting the analysis to studies using the American Academy of Periodontology/European Federation of Periodontology consensus definition from 2017 yielded similar results. The negative impact of periodontitis on OHRQoL was associated with disease severity and female sex but was not influenced by the region or age of the study participants.ConclusionsOur findings confirm that periodontitis significantly impairs OHRQoL, with potential associations related to disease severity and sex. However, the limited availability of studies with matched control groups and poor data reporting quality constrains a more comprehensive assessment.